'A Matter of History': - Nathan Sentance (Public History Review, 2021)
Can we engage in the discussion around colonial monuments if we not are prepared to engage in potentially uncomfortable conversations about our shared history? This commentary asks this and questions why we velementally defend colonial monuments? Is it about history or something else?